POTENSI KERUKUNAN DAN KONFLIK UMAT BERAGAMA DI KOTA MADIUN JAWA TIMUR - Suhanah Suhanah (Harmoni, 2012)
This study used a qualitative approach in the case of harmony, conflict and religious conflict solutions in the city of Madiun. The study concludes that: the potential for harmony in the City of Madis on emerged due to the solidarity of public awareness, where people are ready to be different and agree to maintain the unity and integrity. Given that awareness, religious issues are submitted to the respective religious community through each interfaith leader. In addition, the presence of FKUB and Islamic boarding school has been very effective to support the proper development of living in harmony and effective communication (silaturahmi) among interfaith leaders. Law enforcement and government agencies have promoted the creation of inter-faith harmony in the society. The issue that caused the conflict was recognized by the authorities and wider public. Strategic measures to overcome the internal and inter-religious conflicts through mediation and dialogue with the principle of kinship.